1998
DOI: 10.1038/nm0198-092
|View full text |Cite
|
Sign up to set email alerts
|

The antibiotic rifampicin is a nonsteroidal ligand and activator of the human glucocorticoid receptor

Abstract: The glucocorticoid receptor (GR) belongs to a superfamily of ligand-regulated nuclear steroid hormone receptors. The steps in the signal transduction pathway leading to the biological effects of glucocorticoids (GCs) include sequentially binding of the steroid to the GR ligand binding domain (LBD), receptor transformation, nuclear translocation and either positive or negative gene transactivation. Rifampicin (RIF) is a macrocyclic antibiotic used as an antituberculosis agents. As the incidence of tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
4
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 33 publications
2
55
4
2
Order By: Relevance
“…The mechanism of GR activation in a ligand-independent manner has been the subject of several recent investigations (27,28). In this study, we demonstrate ligand-independent activation of GR by two ␤ 2 -agonists, salmeterol and salbutamol.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of GR activation in a ligand-independent manner has been the subject of several recent investigations (27,28). In this study, we demonstrate ligand-independent activation of GR by two ␤ 2 -agonists, salmeterol and salbutamol.…”
Section: Discussionmentioning
confidence: 99%
“…4) It has also been described as an immunosuppressive drug, 5) and it was shown recently that rifampicin and analogues have the potential to block tumour necrosis factor (TNF)-or phorbol myristate acetate (PMA)-induced, nuclear factor kappaB (NF-kB) activation in the Jurkat T-cell line.…”
mentioning
confidence: 99%
“…Rifampicin may also inhibit the secretion of IL-1β and TNF-α (26). Calleja et al demonstrated that rifampicin both binds to, and activates, the human glucocorticoid receptor, which regulates the expression of many genes, including those encoding interleukins that regulate immune responses (27). Most recently, Dubrac et al established that pharmacologic activation of pregnane X receptor (PXR) inhibits T-lymphocyte function (28).…”
Section: Resultsmentioning
confidence: 99%